Pelatihan Penggunaan Media Sosial Dan Shopee Partner Dalam Upaya Meningkatkan Kewirausahaan Berbasis Produk Lokal di Desa Cilember - Abdul Rohman; Asifa Turahma; Adelia Putri Sumiati; Zahara Nur Sifa; Fitri Widiyanti; Adam Rabbani; Nandita Azzahra Wiguna; Ajeng Ameliya (JPPkM: Jurnal Pengabdian dan Pemberdayaan kepada Masyarakat, 2025)
Poverty alleviation efforts need to begin with a situational analysis and identification of regional potential as a means of community empowerment. One approach that can be used is developing entrepreneurship based on local potential. This program aims to improve community skills in utilizing social media and the Shopee Partner platform for marketing local products. The method used is descriptive qualitative, with stages of training, mentoring, and evaluation. The activity was carried out in Cilember Village, Cisarua District, Bogor Regency, which has local potential in culinary products and agricultural products. The results of the activity showed an increase in community knowledge and skills in using social media as a marketing tool. The conclusion of this community service is that social media-based digital marketing training can significantly increase village community entrepreneurship.